Impaired fasting glucose, type 2 diabetes mellitus, and lifetime risk of cardiovascular disease among women and men: the Rotterdam Study - Lana Fani; Alis Heshmatollah; M Kamran Ikram; Maryam Kavousi; Kan Wang; Fariba Ahmadizar; Elif Aribas (BMJ Open Diabetes Research & Care)
Introduction Data on sex-specific lifetime risk of cardiovascular disease (CVD) across the glycemic spectrum, in particular in impaired fasting glucose (IFG) state, are scarce. Whether overweight/obesity modifies the CVD burden also remains unclear.Research design and methods Using a prospective population-based Rotterdam Study, normoglycemia, IFG, and type 2 diabetes mellitus (T2D) were defined. First incident cases of coronary heart disease, heart failure, and stroke during a follow-up time until January 1, 2015 were identified and formed the composite CVD end point. The remaining lifetime risks of CVD were estimated in each glucose category at 55, 65, 75, and 85 years of age, using a modified version of survival analysis adjusted for the competing risk of death.Results Among 5698 women and 3803 men free of CVD at baseline, the mean age was 64.5 years (SD 9.6) and 60.0% of participants were women. At age 55 years, the remaining lifetime risk of any CVD event among women was 55.1% (95% CI 48.3 to 61.9) for IFG, compared with 52.7% (95% CI 49.5 to 55.9) for normoglycemia and 61.5% (95% CI 54.7 to 68.3) for T2D. For men, the remaining lifetime risk of any CVD event was 62.1% (95% CI 55.2 to 69.1) for IFG, compared with 59.1% (95% CI 55.5 to 62.7) for normoglycemia and 60.3% (95% CI 53.1 to 67.5) for T2D. At age 55 years, the lifetime risk for incident CVD was higher, although not statistically significant, among women and men with IFG who were overweight or had obesity compared with normal-weight women and men.Conclusion IFG carried a large lifetime risk for incident CVD among both women and men compared with normoglycemia. In particular among men, the risk was comparable to that of T2D. Overweight/Obesity modifies the risk and conferred a larger burden of lifetime CVD risk among women and men with IFG.